2006
DOI: 10.1111/j.1749-4877.2006.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Chinese skink,Eumeces chinensis: is prey size important?

Abstract: The diet of the skink, Eumeces chinensis (Lacertilia: Scincidae), in Xiamen (Amoy), China was examined using stomach analysis during April and May, and its selection of prey size was tested by feeding trials. Insects (primarily Coleoptera, Lepidoptera, and Orthoptera), gastropods and arachnids constituted most of the E. chinensis diet, but earthworms, leeches, crustaceans and fish were also consumed. In the field, male skinks ate more prey items that were 11-20 mm in length than other size classes. When presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The effects of size on prey recognition have also been reported in several species of lizards (e.g. Burghardt 1964; Chen and Jiang 2006; Cooper and Stankowich 2010). The skink Plestiodon chinensis , for example, eats more prey of 11–20 mm in length than those of other lengths (Chen and Jiang 2006).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The effects of size on prey recognition have also been reported in several species of lizards (e.g. Burghardt 1964; Chen and Jiang 2006; Cooper and Stankowich 2010). The skink Plestiodon chinensis , for example, eats more prey of 11–20 mm in length than those of other lengths (Chen and Jiang 2006).…”
Section: Discussionmentioning
confidence: 70%
“…Burghardt 1964; Chen and Jiang 2006; Cooper and Stankowich 2010). The skink Plestiodon chinensis , for example, eats more prey of 11–20 mm in length than those of other lengths (Chen and Jiang 2006). Because the handling time (until completely swallowing the prey) increases exponentially as prey size increases over 25 mm, it has been suggested that size preference in P. chinensis maximizes the rate of energy intake (Chen and Jiang 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One way animals can maximize feeding efficiency is to maximize their instantaneous rate of energy intake (DeBenedictis et al . ; Schmid‐Hempel, Kacelnik & Houston ; Chen & Jiang ; Kim, Gilet & Bush ). For example, specialist nectarivores typically prefer higher concentrations of sucrose over weaker ones as stronger solutions allow a higher rate of instantaneous energy intake, up to the point where viscosity imposes physical constraints on consuming (Hainsworth & Wolf ; Roberts , ; Blem et al .…”
Section: Introductionmentioning
confidence: 99%
“…Todavia, presas excessivamente grandes podem causar danos físicos ao predador, representando grande risco ou custo adaptativo (DIETL, 2003;FORBES, 1989;RUTTEN et al, 2006). Por outro lado, presas demasiadamente pequenas são fáceis de serem capturadas e manipuladas, mas podem ser insuficientes para o predador, em termos energéticos (CHEN;JIANG, 2006;FOSSETTE et al, 2011). Em espécies sociais, o valor energético das presas é um fator ainda mais importante, pois deve ser suficiente para manter toda estrutura da colônia (WARD; WEBSTER, 2016).…”
Section: Introdução Geralunclassified
“…However, larger prey can cause injury to the predator (Forbes 1989, Dietl 2003, Rutten et al 2006 and the time spent weakening and handling the prey may also be excessive (Rovero et al 2000). Conversely, small prey can be easier to kill and handle, but the amount of energy they provide may be insufficient (Chen andJiang 2006, Fossette et al 2011). The overall benefits of small prey may therefore not surpass the costs; for social species, these costs include the size of the group and the requirement to share the food (Ward and Webster 2016).…”
Section: Introdução Geralmentioning
confidence: 99%